Sex-comparative study of gambling disorder regarding alexithymia and symptoms of depression, anxiety and hostility - Laura Macía; Paula Jauregui; Marta Herrero; Iciar Iruarrizaga; Virtu Micó; Juan Lamas; Ana Estévez (Comprehensive Psychiatry, 2023)
Background and aims: Alexithymia and psychological symptomatology have been closely associated with gambling disorder (GD). However, sex differences remain underexplored. This study aims, firstly, to explore the differences between groups (GD and no-GD) and sexes (women vs. men) in alexithymia and psychological symptomatology (depression, anxiety and hostility). Secondly, the relationship between alexithymia and psychological symptomatology was analysed by gambling and sex groups. Thirdly, it examines the moderation role of sex and gambling in the relationship between alexithymia and each psychological symptom. Method: The sample was composed of 80 people with GD diagnosis and 80 without GD (40 women and 40 men in each group). Results: The results showed that alexithymia is positively related to depression, anxiety and hostility, with significantly higher scores in people with GD. Moderation analyses showed a threefold interaction, in which higher alexithymia was related to higher depression for men with GD but not for GD-women. However, in women with GD, depression levels are higher than in people without GD and tend to be more stable over time, despite the lack of effect of alexithymia. Conclusions: These results provide evidence indicating that dysfunctional psychological symptomatology affects people with GD to a greater extent than people without GD, but also that the aetiology and effect of underlying vulnerability factors on gambling is different according to sex. The need of prevention and treatment programmes that consider different psychological aspects depending on sex is reinforced.